IMPACT OF WORK FAMILY CONFLICT AND WORK LOAD OF THE EMPLOYEE WOMEN - Aldisa Arifudin; Eldes Willy Filatrovi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this research is to investigate the effects of work family conflict, work stress, work load and turnover intention. The study was conducted at women workers in the banking company. The data is processed using the Structural Equation Modeling (SEM) roomates assisted by the application program of Analysis of Moment Structure (AMOS) version 18.0. According to the analysis, it is concluded as the followings: work family conflict has a positive effect on work stress (CR = 2.347); work load has a positive effect on work stress (CR = 4.472); work family conflict has a effect on turnover intention (CR = 2.084); work load has a positive effect on turnover intention (CR = 2.208) and work stress has a not effect on turnover intention (CR = 1.616) Keyword: Work Family Conflict, Work Stress, Work Load, Turnover Intention